SMOKING AND PERIODONTAL DISEASE: A COMPREHENSIVE REVIEW (The Research of Medical Science Review, 2025)
Periodontal disease is a kind of disease that affects tooth-supporting tissues. Whenever dental plaque accumulates in the gingival sulcus or supragingival area, it can cause inflammation of the gingiva, a condition known as (plaque-induced) gingivitis. If it (inflammation) spreads into underlying supporting tissues and causes destruction of connective tissue that leads to a periodontal pocket, which is called chronic periodontitis, it can be significantly influenced by various factors, such as systemic conditions, host responses, or environmental factors. Among these factors, tobacco use (smoking) is one of the environmental factors. It has various systemic effects, such as causing cancers, chronic obstructive pulmonary disease, cardiovascular disease, pregnancy problems, cataracts, osteoporosis, and periodontitis. Nicotine (the main ingredient of tobacco), which is rapidly absorbed through inhalation or diffusion across the buccal mucosa. About up to two hours after smoking, gingival fibroblasts can continue to absorb and release nicotine, which is found in saliva and gingival fluid, profoundly influencing the composition of the subgingival biofilm. Cotinine (a metabolite of nicotine) can increase collagenase activity, reduce fibroblast adhesion and proliferation, and decrease synthesis of fibronectin and collagen. This article will discuss an overview of the available data in order to give dental health professionals a better understanding of the relationship between smoking and periodontal disease and the impact of smoking and its cessation on the pathogenesis and treatment of periodontal diseases.